VIBRATION SIGNATURE IN HORIZONTAL DIRECTION OF MISALIGNED BALANCE FIXED COUPLING - METHEW NAPITUPULU (NIM : 13104101); Pembimbing : Prof. Dr. Ir. Komang Bagiasna , GERRY
Rotating machines failure generally defected by unbalance and shaft misalignment. These failures can be fixed by balancing and alignment process. In this research, the coupling and pulley of set up were balanced first. Proper balancing process was carried out to minimize 1xRPM rotor vibration signal. The next step is measuring the vibration level of misalignment to detect the characteristic of vibration response. The types of vibration response measurement are power spectrum and spectral map. Vibration magnitude that measured by accelerometer detected the higher signal of 2xRPM for horizontal and axial directions caused by parallel misalignment. For angular misalignment, the vibration magnitude measured by accelerometer detected the higher signal of 1xRPM for vertical, horizontal, and axial directions. The vibration magnitude measured by Laser Doppler Vibrometer (LDV) showed different vibration signature compared to those detected by accelerometers. The result shows that increasing rotorÃ‚Â’s angular speed and misalignment values will increase the overall RMS vibration levels.